2016
DOI: 10.18203/issn.2455-4529.intjresdermatol20163105
|View full text |Cite
|
Sign up to set email alerts
|

Topical corticosteroid abuse on face: a clinical study of 100 patients

Abstract: <p class="abstract"><strong>Background:</strong> Prolonged and uninterrupted use of topical corticosteroids on face is globally prevalant and this misuse has reached monstrous proportion in India. The topical corticosteroid abuse leads to various local adverse effects on face which are difficult to treat. The aim of this study was to ascertain the magnitude, demographics, cause and adverse effects of TC abuse on the face in the dermatology out-patient department.</p><p class="abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…Of the 68 included studies, the indicated data collection period ranged from 1974–1980 to 2015–2016 whereas publication years ranged from 1972 to 2017 . There was a nonwestern preponderance of included studies: Africa ( n = 40), Asia ( n = 18), Middle East ( n = 5), North America ( n = 3), and Europe ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 68 included studies, the indicated data collection period ranged from 1974–1980 to 2015–2016 whereas publication years ranged from 1972 to 2017 . There was a nonwestern preponderance of included studies: Africa ( n = 40), Asia ( n = 18), Middle East ( n = 5), North America ( n = 3), and Europe ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Table presents further characteristics of included studies. A total of 23 (33.8%) studies (lifetime prevalences ≈100%) were not included in estimating the population prevalences (overall, sex‐specific, world region, sample type, data/study period, assessment method, sampling method, and study quality/risk of bias) and the meta‐regression analysis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the incidence of adverse effects due to clobetasol cream was about 42% in this study probably due to d respondents. Study showed hypertrichosis and dermatrophy as common adverse effects due to clobetasol [18,19,20] (Fig. 3).…”
Section: Studies Conducted In Various Countries Includingmentioning
confidence: 97%